Single Inhaler LABA/LAMA for COPD - Malerba, Mario; Foci, Valentina; Patrucco, Filippo; Pochetti, Patrizia; Nardin, Matteo; Pelaia, Corrado; Radaeli, Alessandro (Frontiers in Pharmacology, 2019)
Chronic obstructive pulmonary disease (COPD) is a common disabling disease characterized by progressive airflow obstruction. Great efforts were spent in the development of drugs able to improve symptoms, quality of life, reduce exacerbations, hospitalizations and the frequency of death of patients with COPD. The cornerstones of treatment are bronchodilator drugs of two different classes: beta agonists and muscarinic antagonists. Currently the Global initiative for COPD suggests the use of long acting beta agonists (LABA) and long acting muscarinic antagonists (LAMA) in combination for the majority of COPD patients, thus great interest is associated with the developing of LAMA/LABA fixed combination in the maintenance treatment of stable COPD. Many LAMA/LABA fixed dose combinations have been licensed in different countries and the clinical use of these drugs stimulated the performance of many clinical trials. The purpose of this review is a complete criticism of pharmacological and clinical aspects related to the use of LAMA/LABA single inhalers for the maintenance treatment of stable COPD, with particular mention to the most debated topics and future prospects in the field.